Early palsy of the sciatic nerve due to heterotopic ossification after surgery for fracture of the posterior wall of the acetabulum. - Manidakis, N; Kanakaris, N K; Nikolaou, V S; Giannoudis, P V (J Bone Joint Surg Br, 2009)
We describe a patient in whom an initially intact sciatic nerve became rapidly encased in heterotopic bone formed in the abductor compartment after reconstruction of the posterior wall of the acetabulum following fracture. Prompt excision and neural release followed by irradiation and administration of indometacin resulted in a full neurological recovery and no recurrence 27 months later.
Keywords: Accidental Falls; Acetabulum; Adult; Fracture Fixation, Internal; Hip Dislocation; Humans; Male; Nerve Compression Syndromes; Ossification, Heterotopic; Paresthesia; Postoperative Complications; Radiography; Recovery of Function; Sciatic Nerve; Time Factors; Young Adult